Pelatihan Manajemen Keuangan dan Pelaporan Keuangan pada UMKM Rumah Jamur “NANDO” - Hamdi Agustin; Azwirman Azwirman; Sri Sri Indrastuti; Eny Wahyuningsih (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
The problems faced by business actors at the Nando Mushroom House are: first, the lack of knowledge of business actors about managing their business finances, such as still mixing business and household finances. Second, bookkeeping is still kept simple in their business. The problem that often occurs in home businesses is that household finances are often mixed with business finances. The targets of this Community Service program are: Nando mushroom house business actors are able to do proper bookkeeping and have skills in recording financial posts correctly. The purpose of this service is to provide training in Financial Management and Financial Reporting at the UMKM "NANDO" Mushroom House in Pekanbaru. The solution that can be done is training to make books based on correct accounting standards so that they can accurately calculate and know the profit or loss of their business results. With this financial report, Financial Management and Financial Reporting will be able to manage the finances of the Nando mushroom house. The output produced in this activity is the ability of business actors to carry out proper recording, bookkeeping and financial reporting in order to obtain maximum operating profit. Seeing the resulting output, it is hoped that Nando's mushroom house can develop its business more.